Digital state : the story of Minnesota's computing industry - Misa, Thomas J. (University of Minnesota Press, 2013)
" Accounts of the early events of the computing industry--the Turing machine, the massive Colossus, the ENIAC computer--are well-told tales, and equally well-known is the later emergence of Silicon Valley and the rise of the personal computer. Yet there is an extraordinary untold middle history--with deep roots in Minnesota. From the end of World War II through the 1970s, Minnesota was home to the first computing-centered industrial district in the world. Drawing on rare archival documents, photographs, and a wealth of oral histories, Digital State unveils the remarkable story of computer development in the heartland after World War II. These decades found corporations--concentrated in large part in Minnesota--designing state-of-the-art mainframe technologies, revolutionizing new methods of magnetic data storage, and, for the first time, truly integrating software and hardware into valuable products for the American government and public. Minnesota-based companies such as Engineering Research Associates, Univac, Control Data, Cray Research, Honeywell, and IBM Rochester were major international players and together formed an unrivaled epicenter advancing digital technologies. These companies not only brought vibrant economic growth to Minnesota, they nurtured the state's present-day medical device and software industries and possibly even tomorrow's nanotechnology. Thomas J. Misa's groundbreaking history shows how Minnesota recognized and embraced the coming information age through its leading-edge companies, its workforce, and its prominent institutions. Digital State reveals the inner workings of the birth of the digital age in Minnesota and what we can learn from this era of sustained innovation."--